“SPECTACLE GALLERY” MUARA BARU - Wendy Wennas; F. Tatang H. Pangestu2 (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The development of the city of Jakarta began in the seafront area, which later developed into the city center as a port. For example, the Sunda Kelapa Harbor, has been used since the time of Tarumanegara and is often contested to control trade. Now coastal areas are starting to be abandoned because they continue to experience disasters. Close to the port, in the Muara Baru area, there is a mosque that has sunk due to an old embankment that collapsed by the tidal flood and is now a blind witness that Jakarta will sink. In the past, the area was active; there were many fishing activities and routine recitations. Now the area is limited by a new 4 meter high embankment and the availability of facilities and infrastructure is also insufficient. Because of this, the identity of the area becomes negative and continues to experience physical, social, and mental degradation. So the aim of this project is to provide awareness and innovation to the issue, using the concept of "Spectacle Gallery", i.e., architecture becomes the gallery itself. From the memory of the area to the initial issue of flooding to drowning and the solution of floating houses. Not only that, it aims to revive the area with a positive identity by exhibiting the work of the community from various village points in the area. As a liaison between humans and the surrounding environment, as well as humans with other humans, in accordance with the design theme, namely "Urban Acupuncture". Keywords:  Degradation; Muara Baru; Urban Acupuncture Abstrak Perkembangan Kota Jakarta dimulai pada daerah pinggir laut, yang kemudian berkembang menjadi pusat kota sebagai pelabuhan. Contohnya Pelabuhan Sunda Kelapa, telah dipakai sejak zaman Tarumanegara dan sering diperebutkan untuk mengendalikan perdagangan. Sekarang daerah pesisir mulai ditinggalkan karena terus mengalami bencana. Dekat dengan pelabuhan, di kawasan Muara Baru, terdapat sebuah Masjid yang sudah tenggelam akibat tanggul lama yang runtuh oleh banjir rob dan sekarang menjadi saksi buta Jakarta akan tenggelam. Dahulu wilayah tersebut aktif, terdapat banyak aktivitas nelayan dan pengajian rutin, sekarang wilayah tersebut dibatasi oleh tanggul baru setinggi 4 meter dan keberadaan sarana dan prasarana juga tidak mencukupi. Karena hal tersebut, identitas kawasan menjadi negatif dan terus mengalami degradasi fisik, sosial, dan mental. Sehingga tujuan dari proyek ini adalah memberikan kesadaran dan inovasi terhadap isu, menggunakan konsep “Spectacle Gallery” yaitu arsitektur menjadi galeri itu sendiri. Dari memori kawasan terhadap isu awal banjir hingga tenggelam dan solusi rumah apung. Tidak hanya itu, hal ini bertujuan untuk menghidupkan kembali kawasan dengan identitas positif, dengan memamerkan hasil karya masyarakat dari berbagai titik kampung pada kawasan. Sebagai penghubung manusia dengan lingkungan di sekitarnya, serta manusia dengan manusia lainnya, sesuai dengan tema perancangan yaitu “Urban Acupuncture”.